Endoscopic Examinations in Children with Recurrent Abdominal Pain - Pitono Soeparto (Paediatrica Indonesiana, 1989)
Much difficulties are often encountered in finding the underlying cause of recurrent abdominal pain. Clinical features may vary from one patient to the other and occasionally from one episode to the next even in the same child. The recent development of fibre optic endoscopy may well prove to have a useful diagnostic technique, particularly in those children in whom other investigations are inconclusive. The result of endoscopic examinations in children with recurrent abdominal pain comprising of 62 children aged between 3-13 years were as follows: erosion in 7 children, oesophagi tis in 4 children, duodenitis in 3 children, spasm of the pylorus in 2 children, and normal findings were found in 30 children. Of the 30 patients with "normal" endoscopic findings, 7 had psychosomatic problems, 4 had allergy, 4 had urinary tract infection, 2 showed giardiasis, one had epilepsy, 1 was treated as pulmonary tuberculosis, where as in 11 patients organic as well as nonorganic abnormalities could not be found. There seem to be of no significant correlation between the endocopic and upper gastrointestinal series findings. Endoscopy seem to be of a safe and reliable tool in the diagnosis of a number of organic intestinal lesions otherwise not detected by ordinary investigations.